SIPANDUK Application: E-Government Innovation for the Effectiveness of Population Administration Services in Kuningan Regency - Putri, Intan Sandika; Rismayanti, Rima; Siswoyo, Mukarto; Imawan, Khaerudin (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research is motivated by the development of the SIPANDUK application by Disdukcapil Kuningan Regency to facilitate access to population administration services online. However, its implementation still faces obstacles, such as low public knowledge, less user-friendly application displays and unstable network connections. This study aims to analyze the effectiveness of the SIPANDUK application, identify barriers to its use and formulate solution strategies. Using a descriptive qualitative method through interviews, observations and literature studies, this research refers to Budiani's (2007) theory of program effectiveness with four indicators: program objectives, program socialization, program target accuracy and program monitoring. The results show that the SIPANDUK application is not yet optimal. Socialization strategies and program monitoring are needed to ensure this application provides maximum benefits to the community.